THE EFFECT OF PAY EQUITY and TRUST ON ORGANISATIONAL COMMITMENT: DOES LOVE OF MONEY MATTER? - JARRAR, MOHAMMAD KHAIR GHAZI (2020)
The robust role of organisational commitment through effecting employees’ outcomes leads managers and social scientist to pay close attention to this concept, but to gain and retain employees still represents a big challenge for both. Despite extensive studies concerning organisational commitment (OC), there is still no answer concerning the main factors influencing OC. Previous studies either focused on the antecedents or consequences and not individual differences, particularly inequity or unfairness of distributive justice. This study combines the psychology of money and the love of money (LoM) constructs together with pay equity, trust in leadership and distributive justice to find the key factors that affect OC. However, LoM as an individual difference cannot be overlooked. The need to identify the key factors that could affect OC has been confirmed by the existing literature and many studies have been conducted to find those factors but have failed to focus on individual differences. This study expands on the literature and uses commitment theory to find the major factors that influence organisational commitment A mong 505 locals and expatriate employees working in different public and private organisations with different types of businesses in the United Arab Emirates (UAE). The study examines the moderating effect of the LoM on the relationships between pay equity, trust in leadership and OC. This study adopted a positivist philosophy and a quantitative deductive approach. Data were collected by using both an online survey and a self-administered hard copy survey questionnaire that was completed by locals and expat employees. The data were analysed using the Statistical Package for the Social Sciences (SPSS) and structural equation modelling (AMOS) using multiple regression, path and moderation and mediation analysis. It was found that LoM moderates the relationship between pay equity and both affective and continuance commitment, and moderates the relationship between trust in leadership and affective and continuance commitment, whereas, LoM did not moderate relationships with normative commitment. Both relationships between inequity and injustice with OC are based on the level of the LoM. Therefore, LoM plays a crucial role by affecting employees’ reactions and their decisions to leave or stay in the workplace. The role of LoM influences the second path when it combines with distributive justice and how it influences trust. Based on the importance of pay equity in explaining distributive justice it could be a cornerstone of the model and control employees’ relationships in the workplace. To my knowledge, this is the first empirical study that examines the moderating effect of the LoM on the relationships between pay equity, trust in leadership and OC by using the psychology of money theory represented to investigate the major factors affecting OC. Most previous studies have used pay equity, trust and distributive justice theories separately to find these effects without accounting for the individual factors that may influence OC or affect employee decisions to stay or leave the organisation. Most LoM studies have also focused on the relationships with pay level with lack of studies in regards to employee leaving decision. This study examined whether LoM affects employees’ decisions to stay or leave, which affects OC. This study contributes to knowledge by presenting a conceptual model, which builds on and improves the existing models of pay equity, trust in leadership and OC models, by introducing LoM as a moderator. It explains the importance of the LoM on these relationships. This study proposes a simple explanation that organisational commitment has not stimulated or motivated employees to commit to their work. In other word pay equity or trust in leadership can have some effect on OC, but it can do more by combining LoM. The study recommends that combining LoM into pay equity and trust paths will ensure strong policies for pay equity to heighten OC. The trust in leadership effect cannot work as an effective factor unless the leader adopts equity with their employees, especially if they have employees with high levels of LoM. The effective role of trust will be exposed to the moderating effect of LoM and diminish the effective role of trust. Finally, the process of changing human behaviour is difficult, but adopting equity and distributive justice will retain employees and heighten OC. Therefore, management should identify employees’ LoM levels before implementing any equity systems to ensure that employees are satisfied. Thus, a decision-maker needs to pay attention to the LoM level of their employees and consider it in their future planning and strategies. Further implications of the findings and future research guidelines are also presented.